The Facts on File Encyclopedia of Health and Medicine: VOl.2 - Facts on File (Viva Books, 2013)
Featuring contributions from a diverse group of medical professionals - including psychologists, dermatologists, pulmonologists, gynecologists, cardiologists, ophthalmologists, gastroenterologists, and many others - this book covers a range of health topics, from infancy to old age, paying attention to difference between genders and ethnic groups.